KETERAMPILAN MENGELOLA KELAS UNTUK MENINGKATKAN KONSENTRASI BELAJAR ANAK USIA 4-5 TAHUN DI TK ST. YOSEPH NAIKOTEN II KUPANG - Aelerdis Basa Maing, Maria; Novyani Seran, Theodorina; Olga Litna, Kamelia; Nama Koten, Angelikus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning concentration of children aged 4–5 years at TK St. Yoseph Naikoten II Kupang, as indicated by several children who had difficulty maintaining attention during learning activities. The study aimed to describe teachers' classroom management skills in improving children's learning concentration. This research employed a descriptive qualitative approach. The participants consisted of two Class A1 teachers and seven children aged 4–5 years. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data validity was ensured through technique triangulation, while data were analyzed through data collection, data reduction, data display, and conclusion drawing. The findings showed that teachers demonstrated good classroom management skills through physical classroom management, time management, interaction management, behavior management, and the creation of a positive emotional atmosphere. These practices supported children's learning concentration, which was reflected in their ability to pay attention to learning materials, respond to teachers' instructions, apply acquired knowledge, express ideas or opinions, demonstrate interest in learning activities, and remain engaged throughout the learning process. The study concludes that teachers' classroom management skills play an important role in improving the learning concentration of children aged 4–5 years by creating a conducive learning environment. Keywords: classroom management skills, learning concentration, early childhood